The Effect of Secondary Metabolites Produced by Serratia marcescens on Aedes aegypti and Its Microbiota - Heu, Katy; Romoli, Ottavia; Schönbeck, Johan Claes; Ajenoe, Rachel; Epelboin, Yanouk; Kircher, Verena; Houël, Emeline; Estevez, Yannick; Gendrin, Mathilde (Frontiers in Microbiology, 2021)
Serratia marcescens is a bacterial species widely found in the environment, which very efficiently colonizes mosquitoes. In this study, we isolated a red-pigmented S. marcescens strain from our mosquito colony (called S. marcescens VA). This red pigmentation is caused by the production of prodigiosin, a molecule with antibacterial properties. To investigate the role of prodigiosin on mosquito-S. marcescens interactions, we produced two white mutants of S. marcescens VA by random mutagenesis. Whole genome sequencing and chemical analyses suggest that one mutant has a nonsense mutation in the gene encoding prodigiosin synthase, while the other one is deficient in the production of several types of secondary metabolites including prodigiosin and serratamolide. We used our mutants to investigate how S. marcescens secondary metabolites affect the mosquito and its microbiota. Our in vitro tests indicated that S. marcescens VA inhibits the growth of several mosquito microbiota isolates using a combination of prodigiosin and other secondary metabolites, corroborating published data. This strain requires secondary metabolites other than prodigiosin for its proteolytic and hemolytic activities. In the mosquito, we observed that S. marcescens VA is highly virulent to larvae in a prodigiosin-dependent manner, while its virulence on adults is lower and largely depends on other metabolites.